Development of KAREB Learning Media (Needs Quartet Cards) to Enhance Students’ Learning Motivation in the Grade IV IPAS Subject on the Topic ‘Me and My Needs’ - Lailiyah, Binti Khoirotul; Masrifatin, Yuni (PGMI, STAI Miftahul Ula Nganjuk, 2025)
Learning media is one of the important factors that play a crucial role in the teaching and learning process. In instruction, teachers usually use learning media as an intermediary to deliver material so that it can be well understood by students. The learning conditions at MI PSM Dadapan, especially in the IPAS subject (Natural and Social Sciences), are still conducted conventionally, namely through lecture-based methods. The limited use of learning media causes students to experience boredom. The media to be developed in this study is a needs quartet card medium, hereinafter referred to as KAREB media (Needs Quartet Cards). This study aims to determine the development of KAREB learning media in the Grade IV IPAS subject on the topic “Me and My Needs” at MI PSM Dadapan and to examine students’ learning motivation toward the use of KAREB learning media in the same subject and topic. This research employs a Research and Development (R&D) approach using the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. Data collection instruments consist of interviews, observations, questionnaires, and documentation. The data analysis techniques used are qualitative and quantitative analysis. The subjects of this study were 19 students. The result of this research and development is a set of needs quartet cards consisting of 44 cards and one card box. Product validation by material and media experts obtained an overall average percentage score of 90.50%, indicating that the media is highly feasible for use. Student responses showed a percentage of 99.12%, teacher responses reached 98.94%, and students’ motivation level achieved a percentage of 98.42%. Therefore, the KAREB learning media (Needs Quartet Cards) is considered suitable for use as an instructional medium.